Influence of Degree of Compaction on Unsaturated Hydraulic Properties of a Compacted Completely Decomposed Granite - Rui Chen; Runqiang Tan; Zhongkui Chen; Yang Ping; Zhen Mei (Geofluids)
It is crucial to understand hydraulic properties, i.e., soil-water characteristic curve (SWCC) and unsaturated permeability function (UPF), of completely decomposed granite (CDG) for relevant engineering projects in southeastern China. Previous studies mainly focused on SWCCs of CDG, whereas UPFs of CDG have not yet been well understood. In this study, the effects of the degree of compaction (DOC) on SWCCs and UPFs of CDG were investigated based on experiments where suction range was from 0 to 500 kPa. The microstructure of soil specimens was then analyzed by mercury intrusion porosimetry (MIP). Furthermore, the UPFs of CDG under different values of DOC were calculated using four prediction models and compared with experimental data. Results showed that the pore volume of specimens at higher DOC was smaller than that at lower DOC, and there were more macropores observed in specimens at lower DOC. Meanwhile, it was found that increasing compaction effort produced negligible influence on the volume of micropores. When the suction was less than 100 kPa, the permeability was reduced with the increase in DOC, due to the decrease of macropore volume. However, the influence of DOC on SWCCs and UPFs became marginal when the suction exceeded 100 kPa. The Fredlund and Xing model provided the best prediction of UPF among the four models when suction was smaller than air entry value (AEV). It is suggested that these models could be improved to capture UPFs at higher suctions than AEV by considering suction-induced volume contraction.